ANALISIS KEUNTUNGAN PADA INDUSTRI RUMAH TANGGA PENGOLAH IKAN DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sari, Desi Ratna; Indrawati, Henny; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: Salting fish is a food a reatively cheap and has good nutritional content. Request Fish every day and the city of Pekanbaru Kabupaten Rokan Hilir Kecamatan Tanah Putih is quite higt, many buyers who buy fish to be used as a side dish food suplplement that can increase profits for businesses dried fish. This study aims to determine how much cost is issued the pocess of salted fish to the fish processing buiness profit in the District of South Sedinginan. This research used primary data obtained from direct interview. Responden were interviewed are entrepreneurs household fish processing industry in the District of South Sedinginan with a sample of 30 respondents amounted to the designated purpose. Data analysis techhniques used are qualitative descriptive. Research findings indicate operated processing home industry become fish anchovies every month issued a cover fee of Rp.2.617.202 while home industry acceptance emounted Rp.3.953.333. General operating profit home industry of salted fish processing is Rp.1.336.13.Key Word :,Cost, business Profit, home industry salted fish